The prevalence of vitamin supplementation in ultraendurance triathletes - Knez, W. L.; Peake. J. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2010)
Utraendurance exercise training places large energy demands on athletes and causes a high turnover of vitamins through sweat losses, metabolism, and the musculoskeletal repair process. Ultraendurance athletes may not consume sufficient quantities or quality of food in their diet to meet these needs. Consequently, they may use oral vitamin and mineral supplements to maintain their health and performance. We assessed the vitamin and mineral intake of ultraendurance athletes in their regular diet, in addition to oral vitamin and mineral supplements. Thirty-seven ultraendurance triathletes (24 men and 13 women) completed a 7-day nutrition diary including a questionnaire to determine nutrition adequacy and supplement intake. Compared with dietary reference intakes for the general population, both male and female triathletes met or exceeded all except for vitamin D. In addition, female athletes consumed slightly less than the recommended daily intake for folate and potassium; however, the difference was trivial. Over 60% of the athletes reported using vitamin supplements, of which vitamin C (97.5%), vitamin E (78.3%), and multivitamins (52.2%) were the most commonly used supplements. Almost half (47.8%) the athletes who used supplements did so to prevent or reduce cold symptoms. Only 1 athlete used supplements on formal medical advice. Vitamin C and E supplementation was common in ultraendurance triathletes, despite no evidence of dietary deficiency in these 2 vitamins